Sinonasal Quality of Life Outcomes After Extended Endonasal Approaches to the Skull Base - Choi, Kevin J.; Ackall, Feras Y.; Truong, Tracy; Cheng, Tracy Z.; Kuchibhatla, Maragatha; Zomorodi, Ali R.; Codd, Patrick J.; Fecci, Peter E.; Hachem, Ralph Abi; Jang, David W. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Introduction Endoscopic endonasal skull base surgery (EESBS) leads to significant alterations in sinonasal anatomy and physiology. However, there is limited data available on quality of life (QOL) outcomes following EESBS.Methods A retrospective review of patients undergoing EESBS from January 2014 to April 2017 was performed. Records were reviewed for clinical history, operative details, and 22-item Sinonasal Outcomes Test (SNOT-22) scores. Unadjusted and adjusted linear regression models were utilized to compare change in SNOT-22 scores from baseline in patients who underwent a simple sella approach (SA) or an extended beyond sella approach (BSA).Results A total of 108 patients were in the SA group, while 61 patients were in the BSA group. SNOT-22 scores were available at baseline and 3 months for 84 patients, while 6-month scores were available for 49 patients. SNOT-22 scores for all patients were not significantly different at 3 months (p = 0.40) or at 6 months (p = 0.58). Unadjusted linear regression model did not show an association between the type of approach and change in SNOT-22 score at 3 months (p = 0.07) and 6 months (p = 0.28). Adjusted regression model showed a significant decrease in SNOT-22 scores at 3 months (p = 0.04) for the BSA group, but there was no significant change in SNOT-22 score at 6 months (p = 0.22).Conclusion Patients undergoing EESBS had no significant change in outcomes at 3 and 6 months. A more extensive BSA was not associated with worse QOL outcomes as measured by SNOT-22.
Keywords: quality of life; SNOT-22; Sinonasal Outcomes Test; skull base surgery; endoscopic surgery; pituitary